In Vitro Infection Dynamics of Wuxiang Virus in Different Cell Lines - Xiaohui Yao; Qikai Yin; Danhe Hu; Shihong Fu; Weijia Zhang; Kai Nie; Fan Li; Songtao Xu; Ying He; Guodong Liang; Xiangdong Li; Huanyu Wang (Viruses, 2022)
Wuxiang virus (WUXV) is a newly discovered Bunyavirales transmitted by sandflies. It is found to infect humans and chickens and can cause neurological symptoms and even death in mice. However, the susceptibility of different hosts and tissue-derived cells to this virus is unclear. In this study, we examined cells derived from murine (BHK-21, N2A), human (HEK-293T, SH-SY5Y), dog (MDCK), pig (PK-15), monkey (Vero), and chicken (DF1), which were inoculated with WUXV at 0.05 MOI, and monitored for monolayer cytopathic effect (CPE). Culture supernatants and cells were collected from 0 to 96 h post-infection, cell viability was determined by trypan blue staining, numbers of infectious virus particles were quantified using plaque tests, and viral nucleic acid contents were determined by RT-qPCR. The presence of WUXV N antigen in infected cells was detected by Western blotting (WB). In response to virus infection, BHK-21, MDCK, and PK-15 cells were characterized by a clear CPE, and we observed reductions in the proportion of viable cells after 96 h. By contrast, no significant CPEs were observed in the other cell lines. We detected increases in viral titers, viral nucleic acid content, and N antigen expression in BHK-21, MDCK, PK-15, HEK-293T, N2A, SH-SY5Y, and DF1 cells post-infection. Vero cells showed no CPE, and the findings for other tests were negative. In conclusion, we tested the susceptibility of different cell lines to WUXV, enhanced our current understanding of WUXV biology at the cellular level, and laid the foundations for further investigation of the underlying virus infection mechanisms.